Pelatihan Pembuatan Produk Sedotan Purun Bagi Mahasiswa Pendidikan Ekonomi Sebagai Upaya Pelestarian Lingkungan Program Ecoliteracy - Dewi Rakhmawati; Hidayati Hidayati; Tonich Uda (FKIP Universitas Palangka Raya, 2023)
As plastic straws increase with large amounts of waste, they will cause pollution and problems for the environment and can even threaten human health. One way to overcome this problem is to use straws that are environmentally friendly both in terms of use and eco-friendly materials. This research uses technology transfer, demonstration and training research types. The research results showed that the participants' enthusiasm was great, reflected in several questions asked to the resource persons. Insights and skills related to how purun straws can be used as an effort to reduce plastic waste and understand ecoliteracy as well as provisions for starting independent entrepreneurship.